2020
DOI: 10.1007/s11657-020-00828-y
|View full text |Cite
|
Sign up to set email alerts
|

The associations between different sleep patterns and osteoporosis based on the Osteoporosis Self-Assessment Tool for Asians

Abstract: Summary Based on the use of Osteoporosis Self-Assessment Tool for Asians (OSTA) to assess osteoporosis risk, we found that short sleep duration and taking a daytime nap had an increased risk of osteoporosis. Purpose To explore the associations between different sleep patterns with osteoporosis. Methods 3659 postmenopausal women (average age of 60 years) were divided into low, middle, and high osteoporosis risk categories based on the Osteoporosis Self-Assessment Tool for Asians (OSTA). After having collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Moreover, results of the previous studies revealed that people with later bedtime had a lower femoral BMD and higher risk of osteoporosis than those with normal sleep duration along with usual bedtime [ 18 , 31 ]. On the other hand, over-sleeping or excess daytime sleep had little effect on BMD [ 32 , 33 ]. Our study did not specifically assess bedtime or daytime sleep due to lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results of the previous studies revealed that people with later bedtime had a lower femoral BMD and higher risk of osteoporosis than those with normal sleep duration along with usual bedtime [ 18 , 31 ]. On the other hand, over-sleeping or excess daytime sleep had little effect on BMD [ 32 , 33 ]. Our study did not specifically assess bedtime or daytime sleep due to lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that too short or too long sleep duration, taking a daytime nap, and poor sleep quality increase the risk of osteoporosis [ 11 30 ]. A large-scale cross-sectional study revealed that women aged over 50 years with sleep duration < 5 h/day had a higher risk of osteoporosis (OR = 7.35; 95% CI 3.43–15.71), and participants with poor sleep quality had 5.57 (95% CI 1.60–19.41) odds of osteoporosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%